Autocrine INSL5 promotes tumor progression and glycolysis via activation of STAT5 signaling. Issue 9 (12th July 2020) - Li, Shi‐Bing; Liu, Yan‐Yan; Yuan, Li; Ji, Ming‐Fang; Zhang, Ao; Li, Hui‐Yu; Tang, Lin‐Quan; Fang, Shuo‐Gui; Zhang, Hua; Xing, Shan; Li, Man‐Zhi; Zhong, Qian; et al.
Abstract: Metabolic reprogramming plays important roles in development and progression of nasopharyngeal carcinoma (NPC), but the underlying mechanism has not been completely defined. In this work, we found INSL5 was elevated in NPC tumor tissue and the plasma of NPC patients. Plasma INSL5 could serve as a novel diagnostic marker for NPC, especially for serum VCA‐IgA‐negative patients. Moreover, higher plasma INSL5 level was associated with poor disease outcome. Functionally, INSL5 overexpression increased, whereas knockdown of its receptor GPCR142 or inhibition of INSL5 reduced cell proliferation, colony formation, and cell invasion in vitro and tumorigenicity in vivo . Mechanistically, INSL5 enhanced phosphorylation and nuclear translocation of STAT5 and promoted glycolytic gene expression, leading to induced glycolysis in cancer cells. Pharmaceutical inhibition of glycolysis by 2‐DG or blockade of INSL5 by a neutralizing antibody reversed INSL5‐induced proliferation and invasion, indicating that INSL5 can be a potential therapeutic target in NPC. In conclusion, INSL5 enhances NPC progression by regulating cancer cell metabolic reprogramming and is a potential diagnostic and prognostic marker as well as a therapeutic target for NPC. Synopsis: This study reveals that INSL5 promotes tumor progression by regulating cancer cell metabolic reprogramming. INSL5 is a potential diagnostic and prognostic marker as well as a therapeutic target for nasopharyngeal carcinoma (NPC). INSL5 expression levels are elevated in NPC tumor tissue and in the plasma of NPC patients. INSL5 plasma levels are associated with NPC patient outcome. INSL5 promotes tumor progression through an autocrine mechanism involving binding to its receptor GPCR142. INSL5 activates JAK1‐STAT5 signal pathway and promotes glycolytic gene expression, which in turn induces metabolic reprogramming in cancer cells. INSL5‐GPCR142 axis can be a potential therapeutic target for NPC. Abstract : This study reveals that INSL5 promotes tumor progression by regulating cancer cell metabolic reprogramming. INSL5 is a potential diagnostic and prognostic marker as well as a therapeutic target for nasopharyngeal carcinoma (NPC).